Mode I fracture characterisation of FRP-concrete interfaces under dynamic loading - Li, Gen (2020)
Tensile (mode I) fracture between fibre reinforced polymer (FRP) and concrete is found in the FRP strengthened reinforced concrete (RC) structures, especially for structures under dynamic loads. However, currently, there is a lack of studies on the mode I fracture under dynamic loads. The present programme consisted of two sets of experiments to bridge this gap and to obtain the principal interfacial properties of such fracture. Direct tension tests and notched three-point bending tests were used to determine tensile bond strength and fracture energy of the FRP-concrete interface bond, respectively. Digital image correlation (DIC) measurements were used to characterise the fracture process. It was found that the two bond properties were close to those of plain concrete in the quasi-static regime and showed significant dynamic enhancing effect at a loading rate of 20 mm/s. Dynamic increase factor (DIF) equations for the two bond properties were provided to predict the interfacial response of FRP-concrete bond under dynamic loads. As an application example, the two bond properties were used in finite element simulations of the three-point bending tests.